2016
DOI: 10.1007/s00702-016-1638-y
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of taste in Parkinson’s disease

Abstract: It is well known that Parkinson's disease is characterized by a variety of non-motor symptoms. A gustatory deficit is hypothesized to be one of them although few and only cross-sectional studies are available. The aim of our pilot study was to prospectively investigate the taste function in Parkinson's disease patients after some years from the first evaluation (mean follow-up 4.35 ± 0.49 years; time range 3.5-5.6 years). A group of 26 patients was re-examined (16 males and 10 females; mean age 70.9 ± 8.4 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…2,7 In contrast with the proposition that hypogeusia is a late feature of PD, cross-sectional studies have not demonstrated a correlation between PD duration and taste loss, 3,5 and a prospective study assessing longitudinal evolution of hypogeusia in a cohort of 26 patients with PD showed no significant decline in taste over a mean follow-up period of 4.35 years. 8 Furthermore, the ONSET-PD study showed that taste loss, when present, generally occurs 2-10 years before the onset of parkinsonian motor features. 7 In our study, hypogeusia is similar in both iRBD and PD, suggesting that taste impairment begins early in the course of the disease, when the cortical burden of α-synuclein is expected to be low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,7 In contrast with the proposition that hypogeusia is a late feature of PD, cross-sectional studies have not demonstrated a correlation between PD duration and taste loss, 3,5 and a prospective study assessing longitudinal evolution of hypogeusia in a cohort of 26 patients with PD showed no significant decline in taste over a mean follow-up period of 4.35 years. 8 Furthermore, the ONSET-PD study showed that taste loss, when present, generally occurs 2-10 years before the onset of parkinsonian motor features. 7 In our study, hypogeusia is similar in both iRBD and PD, suggesting that taste impairment begins early in the course of the disease, when the cortical burden of α-synuclein is expected to be low.…”
Section: Discussionmentioning
confidence: 99%
“…Hypogeusia is relatively understudied in PD compared with hyposmia. Previous studies have shown impaired taste in PD compared with controls 2‐9 . The timing and the mechanism hypogeusia have not been established; and its prevalence in prodromal PD is uncertain, having never been studied in patients with iRBD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that an association between smell and taste was reported in a multicenter survey, few and cross‐sectional studies have evaluated taste performance in PD . These studies have been carried out often with a relatively small sample by using different measurement methods, which can be potential confounders; it is generally reported that taste could also be affected in PD by showing persistent but slight and stable taste impairments …”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] These studies have been carried out often with a relatively small sample by using different measurement methods, 7 which can be potential confounders 16,17 ; it is generally reported that taste could also be affected in PD by showing persistent but slight and stable taste impairments. 18 In the past decades, the genetic ability to perceive the bitter taste of thiourea compounds, such as 6-npropylthiouracil (PROP) and phenylthiocarbamide (PTC), has gained considerable attention as a paradigm of general taste perception and an oral marker of food preferences and physiological mechanisms. 17,19,20 This statement is based on several findings that have shown that individuals who only perceive PROP at high concentrations or not at all also perceive lower bitterness of other bitter compounds 21,22 and lower sweetness, 23 sourness, 24 pungency, 25 astringency, 26 umami taste, 27 fats, 28 and high-energy foods when compared with those who perceive PROP as more bitter.…”
mentioning
confidence: 99%